Propuesta de Diseño Estratégico mediante el modelo de gestión Balanced Scorecard en la Empresa Ajar Distribuciones SAS, en la ciudad de Villavicencio (2023)
Strategic planning and the Balanced Scorecard (BSC) are two fundamental tools in business management that allow organizations to establish clear goals, design effective strategies and measure their performance in a comprehensive manner; For this reason, when planning strategically, a series of steps must be included in a systematic way through which organizations, such as Distribuciones Ajar SAS in this case, must define their long-term direction and determine the necessary alternatives to achieve objectives. For this reason, in this paper the business environment was analyzed to identify opportunities and challenges, set goals and develop strategies that would make it possible to take advantage of the opportunities offered by the business context. With the elaboration of the Balanced Scorecard, the planning that the organization develops empirically is complemented, it provides a metric that allows it to monitor its organizational performance, not only from the traditional financial point of view, but also incorporates non-financial indicators that reflect the various key perspectives of the organization, in turn assesses the progress made and identifies areas for improvement against the achievement of strategic objectives to achieve long-term success. For the elaboration of the BSC proposal, it was necessary to involve the directors of Distribuciones Ajar SAS in the concept of strategic planning, starting with management, explaining the importance of establishing strategic objectives and indicators that allow performance to be measured to later evaluate based on those goals and improve their performance to achieve sustainability in an increasingly competitive business environment. 9 Keywords: Strategic planning, Balance Scorecard, Strategic objectives, Indicators, Management.